2009
DOI: 10.1038/jcbfm.2009.211
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Uncoupling of Activation Induced Increases in CBF and CMRO2

Abstract: Neurovascular coupling provides the basis for many functional neuroimaging techniques. Nitric oxide (NO), adenosine, cyclooxygenase, CYP450 epoxygenase, and potassium are involved in dilating arterioles during neuronal activation. We combined inhibition of NO synthase, cyclooxygenase, adenosine receptors, CYP450 epoxygenase, and inward rectifier potassium (Kir) channels to test whether these pathways could explain the blood flow response to neuronal activation. Cerebral blood flow (CBF) and cerebral metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
80
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 48 publications
(84 reference statements)
14
80
1
Order By: Relevance
“…109 In the cerebellum, Offenhauser et al 11 found larger initial decreases of tissue pO 2 during inhibition of CBF responses. Mathiesen et al 102 demonstrated initially unaffected CMRO 2 responses during pharmacologically reduced CBF responses after climbing fiber stimulation in the cerebellum.…”
Section: Uncoupling Of Cerebral Blood Flow and Cerebral Metabolic Ratmentioning
confidence: 96%
“…109 In the cerebellum, Offenhauser et al 11 found larger initial decreases of tissue pO 2 during inhibition of CBF responses. Mathiesen et al 102 demonstrated initially unaffected CMRO 2 responses during pharmacologically reduced CBF responses after climbing fiber stimulation in the cerebellum.…”
Section: Uncoupling Of Cerebral Blood Flow and Cerebral Metabolic Ratmentioning
confidence: 96%
“…A similar phenomenon is seen in the brain, where a number of neurovascular coupling mechanisms are believed to operate concurrently to produce functional hyperemia. 45 However, recent studies suggest that one particular neurovascular coupling mechanism, the feedforward mechanism where glial cells release vasodilatory PGE 2 and EETs, is a principal and perhaps dominant mechanism mediating functional hyperemia in the retina. Determining the relative importance of this and other neurovascular coupling mechanisms awaits further experimentation.…”
Section: Summary Of Neurovascular Coupling Mechanismsmentioning
confidence: 99%
“…Recent work has demonstrated, however, that some of these signals do not mediate neurovascular coupling. Specifically, functional hyperemia can occur in the absence of a drop in oxygen [45][46][47] or glucose 48 levels or acidification of the parenchyma, 49,50 demonstrating that O 2 , glucose, and CO 2 do not function as the neurovascular coupling signal. Still, neurovascular coupling could be mediated, at least in part, by adenosine or lactate metabolic signals.…”
Section: Introductionmentioning
confidence: 99%
“…4 A, D,E), suggesting that the muscimol effect required specific interaction with GABA A receptors. Previous studies have indicated that the stimulation-evoked rises in CBF can be reduced by 80 -90% without concomitant reductions in the evoked electrophysiological signal (Offenhauser et al, 2005;Caesar et al, 2008b;Leithner et al, 2010). CF stimulation evokes large rises in lactate that are coupled to rises in synaptic activity and spike rate (Caesar et al, 2008a).…”
Section: Mechanisms Of Activity-driven Cmro 2 Responsesmentioning
confidence: 99%